THE NUTRITIONAL STATUS SENSITIVITY OF THE ASSESSMENT OF NUTRITIONAL STATUS BASED ON MINI NUTRITIONAL ASSESSMENT (MNA) WAS COMPARED WITH PATIENT-GENERATED SUBJECTIVE GLOBAL ASSESSMENT (PG-SGA) IN CANCER PATIENTS UNDERGOING CHEMOTHERAPY IN RSUP. DR. WAHIDIN SUDIROHUSODA MAKASSAR - Anam, Khoirul - (Faculty of Nursing, University of Jember, 2019)
ABSTRACT Background: Chemotherapy is highly recommended for cancer treatment, however can cause some side effects such as nausea and vomiting. This will affect food intake and nutritional status in cancer patients who undergo chemotherapy. Aim: To describe nutritional status based on anthropometry Body Mass Index (BMI), hemoglobin (Hb), Patient-Generated Subjective Global Assessment (PG-SGA) and Mini Nutritional Assessment (MNA) in cancer patients undergoing chemotherapy in RSUP. Dr. Wahidin sudirohusodo Makassar. Methode: This experiment uses a quantitative non-experimental research method with cross sectional approach on 1010 patients, nonprobability sampling with purposive sampling technique on 70 respondents, data collection with interview and observation techniques. Results: Nutritional status based on Body Mass Index (BMI) shows that 39 people (55.7%) had normal BMI values. About 37 people (52.9%) had good / normal nutritional status based on Patient-Generated Subjective Global Assessment (PG-SGA)  while Mini Nutritional Assessment (MNA) reveals 100% of respondents experienced nutritional status problems. Conclusion: Mini Nutritional Assessment (MNA) is the best tool to identify nutritional status of cancer patients that undergo chemotherapy since this instrument is very sensitive and practical. Patient-Generated Subjective Global Assessment (PG-SGA) is good to assess nutritional status in subject who have lost weight drastically and shows signs of subcutaneous fat loss and muscle mass loss. Keyword: Cancer, chemotherapy, body mass index (BMI), Patient-Generated Subjective Global Assessment (PG-SGA), Mini Nutritional Assessment (MNA).